Islamic civil society's strategies and challenges in the democratization process of Nigeria: a study of Jama'atu Izalatil bid'a Wa'iqamatis-Sunnah in Katsina State, 1999-2017 - Umar, Musa Kabir (2019)
The study investigates the strategies of Izala Islamic civil society organization popularly known as ‘Jama’atu Izalatil Bid’a Wa’iqamtis-Sunnah’ in the democratization process of Katsina State-Nigeria. This problem has been militating against the contributions expected of an Islamic civic association towards improving the quality of democratic ideals in the state. This research presents a conceptually yet empirically supported framework to describe the strategies of the Izala in the democratization of Katsina State. In effect, therefore, the lingering Izala strategies crises in the democratization was explored and analyzed. A conflation of the system theory and the religious market theory was used to interpret not only the strategies used by Izala but also examine how the strategies have helped and challenged the democratization of the State. As a case study qualitative research inquiry, the study presents an in-depth analysis of semi-structured interviews conducted with 18 key informants in Katsina State. The secondary data used in the analysis was derived from journal articles and available relevant literature. Nvivo 12 was used and significantly aided in the coding, categorization and data management which produced the themes and sub-themes. Findings revealed that there are myriads of strategies being used by the Izala in the democratization such as political strategies; religious strategies; and socio-economic empowerment strategies. Moreover, it revealed the contributions of the Izala to the development of democratization in the state. The findings further disclosed the problematic issues related to the strategies used by the Izala in the democratization of the state which includes polarization of the society and the group itself; marketization of religion and patronage seeking in government; derogatory and abusive speeches among others. The study recommends constant contact between the state, Izala leaders and politicians to further strengthen the relationship between all the democratic stakeholders of the state to advance the process. Furthermore, apart from recommending better understanding of democratic ideals by the Izala leaders, it is also suggested that there is serious need to establish a religious groups regulatory body to checkmate their political behaviors in the state